Cross‐Cultural and Construct Validity of the Animated Activity Questionnaire. Issue 9 (13th August 2017) - Peter, Wilfred F.; de Vet, Henrika C. W.; Boers, Maarten; Harlaar, Jaap; Roorda, Leo D.; Poolman, Rudolf W.; Scholtes, Vanessa A. B.; Steultjens, Martijn; Hendry, Gordon J.; Roos, Ewa M.; Guillemin, Francis; Benedetti, Maria G.; et al.
Abstract : Objective: The Animated Activity Questionnaire (AAQ) assesses activity limitations in patients with hip/knee osteoarthritis and consists of video animations; the patients choose the animation that best matches their own performance. The AAQ has shown good validity and reliability. This study aims to evaluate cross‐cultural and construct validity of the AAQ. Methods: Cross‐cultural validity was assessed using ordinal logistic regression analysis to evaluate differential item functioning (DIF) across 7 languages. Construct validity was assessed by testing correlations between the AAQ and a patient‐reported outcome measure (PROM) and performance‐based tests. Results: Data from 1, 239 patients were available. Compared to the Dutch language (n = 279), none of the 17 items showed DIF in English (n = 202) or French (n = 193), 1 item showed uniform DIF in Spanish (n = 99) and Norwegian (n = 62), and 2 items showed uniform DIF in Danish (n = 201). In all these languages, the occurrence of DIF did not influence the total score, which remained comparable with the original Dutch version. For Italian (n = 203) versus Dutch, however, 6 items showed uniform DIF, and 1 item showed nonuniform DIF, indicating some problems with the cross‐cultural validity between these countries. With regard to construct validity, the correlations with PROM (0.74) and performance‐based tests (0.36–0.68) were partly as expected (>0.60). Conclusion: The AAQ, an innovative tool to measure activity limitations that can be placed on the continuum between PROMs and performance‐based tests, showed a good overall cross‐cultural validity, and seems to have great potential for international use in research and daily clinical practice in many European countries.